2012
DOI: 10.1007/s00128-012-0544-8
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Levels in Sediments and Mangrove Oysters, Crassostrea rizophorae, from the North Coast of Villa Clara, Cuba

Abstract: Total mercury levels were quantified in sediments and oyster tissues (Crassostrea rizophorae) from the Sagua la Grande River estuary and offshore mangrove keys 19 km downstream of a chlor-alkali plant (CAP) in Villa Clara, Cuba. Relatively elevated total mercury levels were found in sediments from the estuary itself, ranging from 0.507 to 1.81 μg g(-1) dry weight. However, levels were lower in sediments from the keys farther from the estuary. Oyster mercury levels were always acceptable for human consumption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is well known that bivalves as filter feeding animals are able to concentrate heavy metals in their tissue; therefore they can be used for monitoring heavy metal pollution of the environment. Many authors use bivalve tissues for monitoring marine ecosystem health (Yarsan et al 2007;Olivares-Rieumont et al 2012;Shirneshan et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that bivalves as filter feeding animals are able to concentrate heavy metals in their tissue; therefore they can be used for monitoring heavy metal pollution of the environment. Many authors use bivalve tissues for monitoring marine ecosystem health (Yarsan et al 2007;Olivares-Rieumont et al 2012;Shirneshan et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Dı´az-Asencio et al (2009) also reported a significant enrichment of mercury in the estuary sediment in recent years, reaching a maximum level of 2.68 mg.g x1 around 1990. Moreover, Olivares-Rieumont et al (2012) found levels of mercury ranging from 0.190 to 0.690 mg.g x1 dry weigh (dw) in oyster tissues (Crassostrea rizophorae) collected at the Sagua la Grande River estuary and offshore mangrove keys 19 km downstream of CAP.…”
Section: Introductionmentioning
confidence: 99%